2022
DOI: 10.1155/2022/4086499
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterial-Loaded 16-Printed Log Periodic Antenna Array for Microwave Imaging of Breast Tumor Detection

Abstract: This article presents printed log periodic antennas with metamaterials for use in microwave imaging. A single layer of epsilon negative (ENG) metamaterial (MTM) array (1 × 6) of the unit cell is on the radiating patch. Adding a single negative metamaterial structure enhances the properties of far-field antennas, such as radiation pattern and gain, both of which are vital for breast imaging. Two frequency bands exhibit negative permittivity: 3–3.3 GHz and 3.6–4.5 GHz. In the operating band, the proposed antenna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The work done is compared to some of the recent works [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] in literature which is listed in Table 2. It can be observed that in the proposed work, the single tumor in the homogeneous breast phantom and two tumors in the heterogeneous breast phantom are detected clearly.…”
Section: Image Reconstruction Proceduresmentioning
confidence: 99%
“…The work done is compared to some of the recent works [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] in literature which is listed in Table 2. It can be observed that in the proposed work, the single tumor in the homogeneous breast phantom and two tumors in the heterogeneous breast phantom are detected clearly.…”
Section: Image Reconstruction Proceduresmentioning
confidence: 99%
“…The use of the AMC also improves the main beam gain within the bandwidth of operating frequency from 3.94-7.17 dBi to 7.86-10.01 dBi. A metamaterial loaded antenna array with 16 printed log periodic elements for microwave imaging for breast tumour detection was introduced in [28]. In order to attain a maximum gain of 5.5 dBi, an impedance bandwidth of 3 GHz (2-5 GHz), and a reflection coefficient of less than −10 dB, this antenna design is initially developed using a PLPA structure and subsequently a 1 × 6 metamaterial unit cell array.…”
Section: Introductionmentioning
confidence: 99%